Técnicas de modulación para las comunicaciones acústicas no lineales. - Campo-Valera, María; Felis-Enguix, Iván (My University, 2018)
Non-linear acoustics offers a new era in acoustic applications that are currently being exploited in different fields. The non-linear parametric effect, i.e, the appearance of extra harmonics in the spectrum besides the fundamental frequency is a particular feature in nonlinear acoustic and it can be used in the field of communications. In this area, an essential aspect is the study of the best modulation that suits the needs of communication. Thus, this work explains the techniques of non-linear parametric modulation induce harmonics to propagate. On the other hand, there are some types of modulations such as sinusoidal and sweeps beside CPFSK and LFM in linear communications. With all this, a comparative test can be done among all the technique to obtain more precise detection and discrimination of the bits.
Keywords: Acústica submarina; Procesado de señales; Acústica no lineal; Ultrasonidos; Nonlinear acoustic; Modulation; Underwater acoustic communication; Parametric effect